(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Assimilation is a complex process that involves the incorporation of individuals or groups into a dominant culture or society. It encompasses various stages, each representing a different level of integration into the new cultural norms and practices. Understanding the stages of assimilation is crucial for comprehending the challenges and implications faced by individuals or groups during this transformative process. The theme of assimilation and its stages provides a comprehensive framework to analyze and gauge the extent to which individuals or groups are integrated into the dominant culture and society. It highlights the transformative nature of assimilation and the various factors that influence its progression, offering valuable insights into the challenges, benefits, and implications of cultural integration.